2017
DOI: 10.5334/jeps.413
|View full text |Cite
|
Sign up to set email alerts
|

Construal Level Theory and Moral Judgments: How Thinking Abstractly Modifies Morality

Abstract: Research based on construal level theory has shown that whether objects and events are construed as abstract or concrete is a major factor in influencing people's moral judgments. The aim of this literature review is to describe and evaluate empirical research that has investigated the relationship between construal level and moral judgments. Although most reviewed studies show that abstract thinking leads to stronger moral judgments, inconsistencies exist and gaps in the literature remain. This is due to meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…Research has revealed that construal level affects moral judgements (for a recent, if incomplete review, see Mårtensson 2017). The first study to 7 There may be cultural differences here.…”
Section: Construal Level Theory and Moral Judgementmentioning
confidence: 95%
See 1 more Smart Citation
“…Research has revealed that construal level affects moral judgements (for a recent, if incomplete review, see Mårtensson 2017). The first study to 7 There may be cultural differences here.…”
Section: Construal Level Theory and Moral Judgementmentioning
confidence: 95%
“…There is also a stronger sense in which the tension picked out by Forman is perpetuated in psychological space: four of the studies reviewed by Mårtensson (2017) investigated the effect of social distance on moral judgement. All these, including the only high-power replication study in the field (Žeželj and Jokić 2014), found that social proximity leads to weaker moral judgement.…”
Section: Construal Level Theory and Moral Judgementmentioning
confidence: 99%
“…This is because higher-level construals promote the tendency to interpret distant behaviors in terms of decontextualized and abstract dispositions rather than concrete, situational factors (Trope & Liberman, 2010). As will be elaborated in the following paragraphs, this can affect practical processes such as moral judgment (e.g., Agerström & Björklund, 2009;Mårtensson, 2017) and risk-taking behaviors (e.g., Hershfield & Kramer, 2017;Raue et al, 2015).…”
Section: Psychological Distancementioning
confidence: 99%
“…Due to their highly general, schematic, and abstract nature, moral principles constitute high-level constructs with respect to psychologically more distant situations ( Hess et al, 2018 ). As such, although moral behaviors can be interpreted in terms of decontextualized abstract causes and concrete situational factors, considerable evidence has shown that psychologically distant factors (e.g., temporal, spatial, and social) were directly associated with stronger moral judgments with abstract moral causes [see review by Mårtensson (2017) ]. For example, studies found that people attribute actors’ temporally distant immoral behavior to more abstract and dispositional moral causes (e.g., he or she was a selfish person), as opposed to concrete and situational causes ( Agerström and Björklund, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to being learned earlier and their relatively stable and controllable nature, spatial distance may have a more primary nature than other types of psychological distance ( Zhang and Wang, 2009 ; Trope and Liberman, 2010 ). In addition, temporal distance, which forms the basis of CLT, is by far the most frequently used dimension to investigate the relationship between construal level and moral judgments ( Agerström and Björklund, 2009 ; Agerström et al, 2010 ; Mårtensson, 2017 ). Based on the above considerations, two studies were performed to examine the effects of psychological distance on spontaneous justice inferences by manipulating the spatial distance and temporal distance of actions from the perceivers.…”
Section: Introductionmentioning
confidence: 99%